Cosmogenic exposure age evidence for rapid Laurentide deglaciation of the Katahdin area, west-central Maine, USA, 16 to 15 ka. (15th May 2015) - Davis, P. Thompson; Bierman, Paul R.; Corbett, Lee B.; Finkel, Robert C.
Abstract: Katahdin, the highest peak in Maine and part of the second highest mountain range in New England, provides an opportunity to assess the timing and style of continental ice sheet surface lowering during deglaciation. We collected 14 samples from boulders on the adjacent Basin Ponds moraine, from bedrock and boulders on the upper part of the mountain, and from boulders in the surrounding area to estimate the age at which they were exposed by deglaciation of the Laurentide Ice Sheet. Measurements of in situ produced 10 Be, which are consistent with measurements of 26 Al, indicate that the Katahdin edifice became exposed from under ice by 15.3 ± 2.1 ka (n = 6), an age indistinguishable from the adjacent Basin Ponds moraine (16.1 ± 1.2 ka, n = 5). A boulder in the lowlands several km south of the moraine dates to 14.5 ± 0.8 ka, and a boulder deposited at Pineo Ridge, about 170 km SE of Katahdin, dates to 17.5 ± 1.1 ka. These data show that samples collected over an elevation range of 1.6 km and a distance of >170 km all have exposure ages that are indistinguishable within uncertainties. Together these data suggest that the Laurentide Ice Sheet surface dropped rapidly and the ice sheet margin retreated quickly across Maine between about 16 and 15 ka, perhaps influenced by calving of the marine-based ice sheet in the St. Lawrence Lowlands to the north and the Penobscot basin to the south. Highlights: We sampled boulders and bedrock from Katahdin for analysis of 10 Be and 26 Al. The summit and flanking Basin Ponds moraine were deglaciated ∼16–15 ka. The coast was also deglaciated ∼16 ka. Deglaciation occurred rapidly, in both the horizontal and vertical dimensions. Cirque glaciers did not reform on Katahdin following Laurentide Ice Sheet retreat.